Preconcentration and Determination of Ultratrace of Cd(II) in Water Samples Using Dispersive Liquid-Liquid Microextraction with N-Benzoyl-N-phenylhydroxylamine - Moghimi, Ali; Javad Poursharifi, Mohammad (Asian Journal of Chemistry, 2010)
Dispersive liquid-liquid microextraction (DLLME) technique was successfully used as a sample preparation method for graphite furnace atomic absorption spectrometry (GF AAS). In this extraction method, 500 μL methanol (disperser solvent) containing 34 μL carbon tetrachloride (extraction solvent) and 0.00010 g N-benzoyl-N-phenylhydroxylamine was rapidly injected by syringe into the water sample containing cadmium ions. A cloudy solution is formed. The cloudy state resulted from the formation of fine droplets of carbon tetrachloride, which have been dispersed, in bulk aqueous sample. At this stage, cadmium reacts with N-benzoyl-Nphenylhydroxylamine and therefore, hydrophobic complex forms which is extracted into the fine droplets of carbon tetrachloride. After centrifugation (2 min at 5000 rpm), these droplets were sedimented at the bottom of the conical test tube (25 ± 1 μL). Then a 20 μL of sedimented phase containing enriched analyte was determined by GF AAS. Some effective parameters on extraction and complex formation, such as extraction and disperser solvent type and their volume, extraction time, salt effect, pH and concentration of the chelating agent have been optimized. Under the optimum conditions, the enrichment factor 118 was obtained from only 5.00 mL of water sample. The calibration graph was linear in the rage of 2-21 ng L-1 with detection limit of 0.6 ng L-1. The relative standard deviation (RSDs) for ten replicate measurements of 20 ng L-1 of cadmium was 3.1 %. The relative recoveries of cadmium in tap, sea and rain water samples at spiking level of 5 and 10 ng L-1 are 98, 94, 96 and 93 %, respectively. The characteristics of the proposed method have been compared with cloud point extraction, on-line liquid-liquid extraction, single drop microextraction, on-line solid phase extraction and co-precipitation based on bibliographic data. Therefore, dispersive liquid-liquid microextraction combined with graphite furnace atomic absorption spectrometry is a very simple, rapid and sensitive method, which requires low volume of sample (5.00 mL).